PENGARUH PELATIHAN KERJA, KOMPTENSI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BANK BCA KANTOR CABANG CIKARANG UTARA - Halipi Hazizan; Wachid Hasyim; Riski Eko Ardianto (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The achievement of company goals or the success of the company is greatly influenced by the individual performance of employees. Every organization must strive to improve employee performance in the hope of achieving the company's goals. This study aims to analyze the effect of training, competence and work motivation on employee performance. The type of research is quantitative. Research data are primary data from questionnaires and secondary data. The sampling method used is non-probability sampling, the sampling technique uses saturated sampling, the number of samples is 96 people. The analysis method used in this study is multiple linear regression. The results showed that training, competence and motivation have a positive and significant effect on employee performance